From digital literacy to digital resilience in higher education - Shafie, Dalili Izni; Anthanamery, Thominathan (2024)
The term "digital literacy skills" is defined as the set of abilities related to utilizing technology for tasks such as finding, evaluating, organizing, creating, and communicating information. It also involves the development of digital citizenship and the responsible use of technology. This definition has been embraced by many educational, workforce, and digital inclusion initiatives. However, what's notably absent from this definition is the capacity to navigate digital transformation and the continuous acquisition of new technological proficiencies. This aspect has become a pressing concern for adult learners, educators, and program leaders, particularly in the context of the COVID-19 pandemic and the evolving nature of work. Learners have emphasized the necessity for specific digital skills to effectively use the platforms required for both formal and informal work, including opportunities in entrepreneurship and the gig economy. Hence, the concept of "digital resilience" has emerged, which can be defined as the possession of awareness, skills, adaptability, and confidence necessary to empower individuals as users of emerging technologies and to adjust to the evolving demands of digital skills. Digital resilience enhances the ability to tackle challenges, learn new skills, navigate digital transformations, and engage actively in both society and the economy.